The Regulation of Financial and Other Futures Markets: Discussion - Edwards, F. R. (Journal of Finance, 1982)
F. R. Edwards, The Regulation of Financial and Other Futures Markets: Discussion, The Journal of Finance, Vol. 37, No. 2, Papers and Proceedings of the Fortieth Annual Meeting of the American Finance Association, Washington, D.C., December 28-30, 1981 (May, 1982), pp. 517-519